Tolerability and Effects of 2-Aminoethyl Dihydrogen Phosphate in Dogs With Mast Cell Tumors - Januário, Eric Vieira; Melo, Samanta Rios; Maria, Durvanei Augusto; Lorigados, Carla Aparecida Batista; Ambrósio, Aline Magalhães; Kogika, Marcia Mery; Cogliati, Bruno; Shimozako, Helio Junji; Matera, Julia Maria (Frontiers in Veterinary Science, 2022)
Canine mast cell tumor is a malignant neoplasm, and a gold standard treatment remains to be determined despite the proposed chemotherapies or other therapies in dogs. This study aimed to determine therapeutic, adverse effects and toxicity, tumor-free, and overall survival times of 10 dogs with surgically excised mast cell tumors evaluated by histopathological/immunohistochemistry and treated with four weekly intravenous administrations of 2-Aminoethyl Dihydrogen Phosphate (70mg/kg) as adjuvant therapy. No adverse events were noted. Laboratory changes were limited (p < 0.05) in red blood cell, hemoglobin, and platelet counts. Mean tumor-free and overall survival were 599.1 ± 469 and 755.5 ± 423.5 days, respectively. In conclusion, 2-Aminoethyl Dihydrogen Phosphate administration was safe in dogs. However, 2-Aminoethyl Dihydrogen Phosphate was not sufficiently effective to prevent a recurrence, new tumor, or metastasis of canine mast cell tumors with poor immunohistochemical prognostic factors.